2021
DOI: 10.3390/su13115867
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Differentiation of Coupling and Coordination Relationship of Tourism–Urbanization–Ecological Environment System in China’s Major Tourist Cities

Abstract: Determining the coupling development mode and evolution process of the tourism industry–urbanization–ecological environment system is of great significance in promoting high-quality and sustainable development of tourism and the urban economy. In this study, an evaluation index system of the tourism–urbanization–ecological environment system was established, and the spatiotemporal differentiation of the coupling and coordination relationship of the tourism–urbanization–ecological environment system was analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 20 publications
2
39
0
1
Order By: Relevance
“…First, regarding the relationship between tourism and the ecological environment, previous research results have shown that there is a significant coupling relationship between tourism and the ecological environment [57,58]. Tourism is the main driver of carbon emissions, and its thesis of a "smoke-free industry" has been disproved by most studies [16,17]; as such, the rapid development of tourism will undoubtedly damage the ecological environment [56]. With the development of tea culture tourism, it was also found that the comprehensive development level of tourism exceeds the ecological environment, due to problems such as the rapid development of tourism and the lag of the ecological environment level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, regarding the relationship between tourism and the ecological environment, previous research results have shown that there is a significant coupling relationship between tourism and the ecological environment [57,58]. Tourism is the main driver of carbon emissions, and its thesis of a "smoke-free industry" has been disproved by most studies [16,17]; as such, the rapid development of tourism will undoubtedly damage the ecological environment [56]. With the development of tea culture tourism, it was also found that the comprehensive development level of tourism exceeds the ecological environment, due to problems such as the rapid development of tourism and the lag of the ecological environment level.…”
Section: Discussionmentioning
confidence: 99%
“…After reviewing the literature on the coupling coordination between the tea industry, tourism, and the ecological environment, combined with the actual situation of industry, tourism, and the ecological environment in Fujian Province, a coupling coordination evaluation index system of the tea industry, tourism, and the ecological environment of Fujian Province was systematically constructed (Table 1). On the basis of referring to the existing literature on the coupling coordination between the tea industry and tourism [12,18], and that for the tourism industry and the ecological environment [56][57][58], combined with the advice of experts, we determined that efficiency is an important factor in evaluating a system. In the system, the tea industry indices comprise six elements, including tea industry scale and tea efficiency, and the tourism industry indices comprise six elements, including tourism scale and tourism efficiency.…”
Section: Evaluation Index System Constructionmentioning
confidence: 99%
“…In terms of TID, on the basis of the construction of the index system of the existing research [28,34], this study constructed an index system from the industry benefit, industry scale, and industry status of TID, including nine indicators. Among them, industry benefit is the direct reflection of measuring the level of tourism development, which is measured by domestic tourism income, foreign exchange earnings from international tourism, and the annual growth rate of total tourism income.…”
Section: Implementation Of Methodology 231 Construction Of Evaluation Index Systemmentioning
confidence: 99%
“…These cities are well known at home and abroad, where the regional economies are developed, and tourism resources are rich and high quality, attracting a large number of domestic and foreign tourists. Furthermore, the development of the tourism industry in these cities has gained more general market recognition, so they are called "major tourist cities" [28]. Taking this as a case study can better reflect the actual level of China's urban tourism industry.…”
Section: Study Areamentioning
confidence: 99%
“…Tourism consumption and aggregation of the population and industries brought about by tourism development provides impetus for regional development. Moreover, the consumption and production of tourism need to be completed in specific geographical spaces [56].…”
Section: Theoretical Analysis Framework Of Sustainable Tourismizationmentioning
confidence: 99%